Understanding the role of air and protein phase on mechanical anisotropy of calcium caseinate fibers. (July 2019) - Wang, Zhaojun; Tian, Bei; Boom, Remko; van der Goot, Atze Jan
Abstract: Calcium caseinate dispersions can be transformed into anisotropic, fibrous materials using the concept of shear-induced structuring. The aim of this study is to further investigate the relative importance of air bubbles and protein on the mechanical anisotropy of calcium caseinate material. In this study, the effect of air on mechanical anisotropy of these fibrous materials was described with a load-bearing model, with the void fraction, and the bubble length and width as input parameters. The anisotropy of the protein phase was estimated using materials obtained from deaerated dispersions after shearing at different shear rates. We concluded that the deformation of air bubbles can only partly explain the mechanical anisotropy; the anisotropy of the protein phase is more important. Based on all results, we further concluded that the anisotropy of the protein phase was affected by the air bubbles present during the structuring process. This effect was explained by locally higher shear rate in the protein matrix during the structuring process. Graphical abstract: Unlabelled Image Highlights: A load-bearing model is used to describe the fracture stress of the calcium caseinate materials. The anisotropy of the calcium caseinate material comes from the anisotropy in the protein phase and the air. A linear relationship was obtained between mechanical anisotropy of deaerated material and shear rate. Shear force deformed large air bubbles, rather than small ones.